2018
DOI: 10.31783/elsr.2018.411114
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ice massage in reduction of labor pain during first stage of labor among primigravida mothers

Abstract: Labor is a stressful experience that has pain, fatigue, fear and negative moods reaching high levels as labor progresses. The objective of this study was to assess the effectiveness of ice massage in reduction of labor pain between control and experimental group. Quantitative research approach and Quasi experimental after research only design was adopted for this study. Sixty Primigravida mothers at first stage of labor were divided as 30 each in both the experimental and control group. Visual analogue scale w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In this study, ice massage applied to the SP6 point at 4 to 5 cm, 6 to 7 cm, and 8 to 9 cm cervical dilatation reduced perceived labor pain. In other studies, the labor pain levels of cold massage groups have been found to be significantly lower than control groups 3,8,12,13,21,23–25 . The continual stimulation of acupressure points in labor can increase vital energy flow in the meridians, and thus provide more considerable therapeutic effects 21 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this study, ice massage applied to the SP6 point at 4 to 5 cm, 6 to 7 cm, and 8 to 9 cm cervical dilatation reduced perceived labor pain. In other studies, the labor pain levels of cold massage groups have been found to be significantly lower than control groups 3,8,12,13,21,23–25 . The continual stimulation of acupressure points in labor can increase vital energy flow in the meridians, and thus provide more considerable therapeutic effects 21 .…”
Section: Discussionmentioning
confidence: 87%
“…In other studies, the labor pain levels of cold massage groups have been found to be significantly lower than control groups. 3,8,12,13,21,[23][24][25] The continual stimulation of acupressure points in labor can increase vital energy flow in the meridians, and thus provide more considerable therapeutic effects. 21 In studies similar to this study in which acupressure was applied to the SP6 point, it has been reported that labor pain levels of intervention groups are lower compared with those of control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 There are also other studies in which cold massage was applied to Hegu (LI4) point other than SP6 point. 8,12,13,19,26,27 In the studies conducted by Dehcheshmeh and Rafiei (2015), Indumathi (2018), and Afefy (2015), it was reported that ice massage applied to Hegu point for 29 minutes reduced labor pain more compared to the control group. 13,26,28 In the study they conducted, Hajiamimi et al (2012) applied ice massage to Hegu point for 10 minutes in 2-minute rotations, followed by a 15-minute break.…”
Section: Discussionmentioning
confidence: 99%
“…8,12,13,19,26,27 In the studies conducted by Dehcheshmeh and Rafiei (2015), Indumathi (2018), and Afefy (2015), it was reported that ice massage applied to Hegu point for 29 minutes reduced labor pain more compared to the control group. 13,26,28 In the study they conducted, Hajiamimi et al (2012) applied ice massage to Hegu point for 10 minutes in 2-minute rotations, followed by a 15-minute break. As a result, they found that ice massage applied decreased labor pain immediately after the intervention, 30 minutes later, and one hour later.…”
Section: Discussionmentioning
confidence: 99%